Attacks on SVD-Based watermarking schemes - Huo-Chong, Ling; Raphael C. -W., Phan; Swee-Huay, Heng (SPRINGER-VERLAG BERLIN, 2008)
One major application of a watermarking scheme is to protect the copyright of a content owner by embedding the owner's watermark into the content. Recently, two watermarking schemes were proposed by Chang et al. [1, 2], which are based on singular value decomposition (SVD). In this paper, we present attacks on these watermarking schemes and show how the designers' security claims can be invalidated, namely related to robustness and protection of rightful ownership. Our results are the first known attacks on these SVD-based watermarking schemes.